2013
DOI: 10.37570/bgsd-2013-61-01
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy and age of the Eocene Igtertivâ Formation basalts, alkaline pebbles and sediments of the Kap Dalton Group in the graben at Kap Dalton, East Greenland

Abstract: A NE–SW-trending graben at Kap Dalton on the Blosseville Kyst contains an at least 600 m thick succession of Eocene basalt lavas and sediments. The succession has been investigated by new field work, geochemical analysis and radiometric dating by the 40Ar-39Ar incremental heating method. The results show that the volcanic succession comprises about 220 m of the uppermost plateau basalt formation, the Skrænterne Formation. This is separated from the overlying lava flows of the Igtertivâ Formation by 7 m of sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The area between Scoresby Sund and Kangerlussuaq subsided after continental breakup at 56 Ma. This is documented by the Igtertivâ Formation which immediately overlies the Main Basalts of Larsen et al (1989Larsen et al ( , 2013 and includes volcanic flows interdigitated with marine sediments. The volcanic pile of the Main Basalts is up to 6 km thick and was erupted in less than 1 Myr (Pedersen et al 1997).…”
Section: Timing Of Burial and Exhumationmentioning
confidence: 97%
“…The area between Scoresby Sund and Kangerlussuaq subsided after continental breakup at 56 Ma. This is documented by the Igtertivâ Formation which immediately overlies the Main Basalts of Larsen et al (1989Larsen et al ( , 2013 and includes volcanic flows interdigitated with marine sediments. The volcanic pile of the Main Basalts is up to 6 km thick and was erupted in less than 1 Myr (Pedersen et al 1997).…”
Section: Timing Of Burial and Exhumationmentioning
confidence: 97%
“…The first volcanics were partly erupted in a marine environment in Paleocene time. Furthermore, there are marine sediments within the youngest flood basalts, the lower Eocene Igtertivâ Formation, and within the lower Eocene to lower Oligocene Kap Dalton Group (Soper & Costa 1976;Nielsen et al 1981;Larsen et al 1989Larsen et al , 2002Larsen et al , 2013. The presence of marine deposits above and below the Main Basalts, which were extruded on a largely horizontal plain, implies that the landscape was low-lying during the volcanic eruptions.…”
Section: Cenozoic Cover and Unconformitiesmentioning
confidence: 99%
“…Fig.27Post-basalt heating of lower Eocene sediments at Blosseville Kyst(Larsen et al 2013;Japsen et al 2014). End-Eocene C6 palaeotemperatures in three samples (yellow circles) correspond to burial below a c. 2.5 km thick Eocene succession assuming a palaeothermal gradient of 25°C/km and a surface temperature of 20°C.…”
mentioning
confidence: 99%
“…The intrusions are older than the Igtertivâ Formation at Kap Dalton on the Blosseville Kyst which comprises two parts dated at 49.1 ± 0.5 Ma and 43.8 ± 1.1 Ma (Larsen et al 2013). Larsen et al (2013) found significant geochemical differences between the Igtertivâ Formation basalts and the underlying 55 Ma lavas of the Skraenterne Formation, in particular in the rare-earth element (REE) ratios. As seen in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The older magmas were probably generated under similar conditions beneath relatively thick lithosphere. Hald & Tegner (2000), Larsen et al (2013), Larsen et al (2014) and unpublished GEUS data (2008-2010. A few crustally contaminated samples are not plotted.…”
Section: Lml3mentioning
confidence: 95%